Is it time to switch to bivalirudin for ECMO anticoagulation? - Navaei, Amir; Kostousov, Vadim; Teruya, Jun (Frontiers in Medicine, 2023)
For decades, unfractionated heparin (hereafter, heparin) has been the primary anticoagulant used for extracorporeal membrane oxygenation (ECMO) support. More recently, however, bivalirudin, a direct thrombin inhibitor, has emerged as an alternative. This systematic review based on PRISMA guidelines, aims to summarize 16 comparative studies and 8 meta-analysis and review articles published from January, 2011 till May, 2023 which directly compares ECMO courses using heparin versus bivalirudin as the anticoagulant. While this comparison is complicated by the lack of a standardized definition of major bleeding or thrombosis, our overall findings suggest there is no statistical difference between heparin and bivalirudin in incidence of bleeding and thrombosis. That said, some studies found a statistical significance favoring bivalirudin in reducing major bleeding, thrombosis, and the need for transfusions. We also offer essential guidance for appropriately selecting an anticoagulant and monitoring its effect in ECMO settings.